2009
DOI: 10.1007/s10334-008-0160-0
|View full text |Cite
|
Sign up to set email alerts
|

In vivo comparison of atherosclerotic plaque progression with vessel wall strain and blood flow velocity in apoE−/− mice with MR microscopy at 17.6 T

Abstract: This study has demonstrated the application of high-field MRI for characterizing the temporal progression of morphological and mechanical changes to murine aortic vasculature associated with atherosclerotic lesion development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
(42 reference statements)
1
11
0
Order By: Relevance
“…26,27 A recent study from our group indicated that the change in cross-sectional vessel area during systole, a parameter related to vascular elasticity, is already impaired in the early stages of atherosclerosis. 28 The systolic cross-sectional change in vessel area, however, is not an independent parameter of vascular elasticity because it depends on cardiac output. In the presented study, therefore, we assessed the local PWV, which is quantitatively related to the vessel wall elasticity by the Moens-Korteweg equation.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 A recent study from our group indicated that the change in cross-sectional vessel area during systole, a parameter related to vascular elasticity, is already impaired in the early stages of atherosclerosis. 28 The systolic cross-sectional change in vessel area, however, is not an independent parameter of vascular elasticity because it depends on cardiac output. In the presented study, therefore, we assessed the local PWV, which is quantitatively related to the vessel wall elasticity by the Moens-Korteweg equation.…”
Section: Discussionmentioning
confidence: 99%
“…The protocols presented here are not exclusively suitable for imaging the carotid arteries. They can be straightforwardly translated to study the role of flow and wall shear stress in the aortic arch and the abdominal aorta [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, CMR systems did not provide a sufficient SNR to allow for accurate PWV measurements in mice. New high-field CMR systems facilitate a very high SNR and allow for examinations of morphologic and also functional parameters of the arterial system of mice [21,22]. …”
Section: Introductionmentioning
confidence: 99%